2011
DOI: 10.1113/jphysiol.2010.199059
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of reactive oxygen and nitrogen species on the contractile function of skeletal muscle

Abstract: Reactive oxygen and nitrogen species (ROS/RNS) are important for skeletal muscle function under both physiological and pathological conditions. ROS/RNS induce long-term and acute effects and the latter are the focus of the present review. Upon repeated muscle activation both oxygen and nitrogen free radicals likely increase and acutely affect contractile function. Although fluorescent indicators often detect only modest increases in ROS during repeated activation, there are numerous studies showing that manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
144
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 48 publications
11
144
0
2
Order By: Relevance
“…2, A and C), it is likely that Ca 2ϩ uptake rate could not be reduced (39). Thus, the reduced tension of Tg ϩ EDL was associated with a decreased cross bridge dissociation rate, which could be affected by either NO or ROS as shown in the literature (14,24,38,39). These results suggested that chronic production of TNF-␣ likely affected the cross bridge dissociation rate of Tg ϩ EDL under both PO 2 conditions, consistent with the hypothesis by Reid et al (31) that TNF-␣ negatively affected either myosin ATPase activity or the thin-filament Ca 2ϩ kinetics.…”
Section: Discussionmentioning
confidence: 95%
“…2, A and C), it is likely that Ca 2ϩ uptake rate could not be reduced (39). Thus, the reduced tension of Tg ϩ EDL was associated with a decreased cross bridge dissociation rate, which could be affected by either NO or ROS as shown in the literature (14,24,38,39). These results suggested that chronic production of TNF-␣ likely affected the cross bridge dissociation rate of Tg ϩ EDL under both PO 2 conditions, consistent with the hypothesis by Reid et al (31) that TNF-␣ negatively affected either myosin ATPase activity or the thin-filament Ca 2ϩ kinetics.…”
Section: Discussionmentioning
confidence: 95%
“…Although troponin I harbours several cysteine residues, some of these cysteines are insensitive to Ca 2+ -induced conformational changes in native troponin I (Chong and Hodges 1981). Therefore, the impaired contractility could, in part, be unrelated to reduced Ca 2+ concentrations but might instead be due to the oxidation of amino acids in myofilament proteins (Gao et al 1995;Gao et al 1996;Andrade et al 1998Andrade et al , 2001Lamb and Westerblad 2011). In spite of suggestions that SH oxidation of tropomyosin and/or actin in combination with myosin light chain1 (MLC1) (Hertelendi et al 2008) are potential mediators of oxidative myocardial contractile depression, it is currently difficult to clearly state that oxidation of myofilament proteins causes cardiac dysfunction, since studies have reported equivocal effects in different muscle types and even within a single muscle type.…”
Section: Impact Of Oxidative Stress On Cardiomyocyte Stiffness Sarcommentioning
confidence: 99%
“…For a detailed description of the potential sources of exercise-induced reactive species production, the reader is referred to specific reviews (Sjodin et al, 1990;Jackson et al, 2007;Sachdev and Davies, 2008;Lamb and Westerblad, 2011;Powers et al, 2011c).…”
Section: Multiple Sources and Tissues Generate Reactive Species Durinmentioning
confidence: 99%